Modulatory responses of physiological and biochemical status are related to drought tolerance levels in peanut cultivars - Checchio, M. V. [UNESP]; Bacha, A. L. [UNESP]; Carrega, W. C.; da Silveira Sousa Júnior, G.; da Costa Aguiar Alves, P. L. [UNESP]; Gratão, P. L. [UNESP] (Wiley, 2025)
Peanut (Arachis hypogaea L.) is the fourth most cultivated oilseed in the world, but its cultivation is subject to fluctuations in water demand. Current studies of tolerance between cultivars and physiological mechanisms involved in plant recovery after drought are insufficient for selection of tolerant cultivars. We evaluated tolerance of different peanut cultivars to water deficit and subsequent rehydration, based on physiological and biochemical status. Gas exchange, photosynthetic pigments, Fv/Fm, MDA, H2O2 and antioxidant enzyme activity were analysed. Drought stress and rehydration triggered distinct changes in pigments, Fv/Fm, gas exchange, and H2O2 across genotypes, with increased MDA in all cultivars under stress. Based on multivariate analysis, ‘IAC Sempre Verde’ was identified as most drought sensitive, while ‘IAC OL3’, ‘IAC 503’, and ‘IAC OL6’ exhibited variations in physiological responses and antioxidant activity correlated to their respective tolerance levels. Notably, ‘IAC OL3’ had higher WUE and enhanced enzymatic defence and was classified as the most drought tolerant in this context. The above findings suggest that antioxidant metabolism is a important factor for plant recovery post-rehydration. Our study provides insights into antioxidant and physiological responses of peanut cultivars, which can support breeding programs for selection of drought-tolerant genotypes. Future field studies should be conducted for a better understanding of tolerance of these cultivars, particularly through correlation of these data with crop yield impact.
Keywords: Abiotic stress; antioxidant enzymes; Arachis hypogaea L.; gas exchange; water deficit